Mediastinoscopic esophagectomy for patients with early esophageal cancer - Wang, Qian-Yun; Li, Jing-Pei; Zhang, Lei; Jiang, Nan-Qing; Wang, Zhong-Lin; Zhang, Xiao-Ying (Journal of Thoracic Disease, 2015)
Objective: The purpose of this study was to detect the feasibility, safety, and effectiveness of mediastinoscopic esophagectomy for early esophageal cancer. Methods: The clinical data of 194 patients who underwent mediastinoscopic esophagectomy for early esophageal cancer in our center from December 2005 to October 2014 were retrospectively analyzed. Results: All the surgery was performed successfully. The average duration of thoracic surgery was 48.2±7.8 min and the average intra-operative blood loss was 128.1±34.5 mL. An average of 3.1±1.6 lymph node stations were dissected, with an average number of dissected lymph nodes being 9.38±6.2, among which 4.2±5.4 were mediastinal lymph nodes. No peri-operative mortality was noted, and the rate of peri-operative morbidity was 13.4%. The median duration of follow-up was 39 [3-108] months, and the overall survival was 72.73%. The overall survival rates significantly differed among different T stages; more specifically, the 5-year survival was 95.23% in patients with stage T1a esophageal cancer, 70.15% for T1b, and 55.56% for T2 (P